Microstructural elucidation of self-emulsifying system: effect of chemical structure - Patil, Sharvil S.; Venugopal, Edakkal; Bhat, Suresh K.; Mahadik, Kakasaheb R.; Paradkar, Anant R. (Pharmaceutical Research, 2012)
Self-emulsifying systems (SES) emulsify spontaneously to produce fine oil-in-water emulsion when introduced into aqueous phase. The self-emulsification process plays an important role during formation of emulsion. The objective of current work was to understand and explore the inner structuration of SES through controlled hydration and further to study the influence of additive on the same which ultimately governs performance of final formulation in terms of droplet size. Droplet size of final formulations containing structural analogues of ibuprofen was determined. Microstructural properties of intermediate hydrated regimes of SES were investigated using techniques such as small angle X-ray scattering, differential scanning calorimetry and rheology. The current work established inverse relationship between droplet size of the formulations containing structural analogues of ibuprofen and their Log P values. Microstructural analysis of intermediate hydrated regimes of the prepared samples showed formation of local lamellar structure. Structural analogues of ibuprofen significantly altered microstructure of lamellae which was well correlated with the droplet size of final formulations. In vitro drug release study showed increase in dissolution rate of lipophillic drugs when formulated as SES. The current work emphasizes the fact that tailor-made formulations can be prepared by controlling the properties of intermediate regimes.
Keywords: emulsion; flurbiprofen; ibuprofen; ketoprofen; lamellar structure; self-emulsifying system; structural analogues